PLEUROPULMONARY SALMONELLA INFECTION – A CASE REPORT - Pavic, Sladjana M; Pavic, Aleksandra; Novkovic, Aleksa (Sanamed, 2025)
Introduction: Invasive nontyphoidal salmonellosis occurs in 5–10% of all nontyphoidal Salmonella infections, with an increasing trend, even in non-endemic areas. Extraintestinal manifestations may include inflammation or abscess formation in various organs, such as the lungs, meninges, kidneys, testes, muscles, and gallbladder.Case report: We present the case of a 65-year-old female patient admitted for treatment due to fatigue, dyspnea, and weight loss. She did not report diarrhea or fever, and no epidemiological factors suggested a gastrointestinal infection.Her medical history included hypertension and long-term heavy cigarette smoking.A chest X-ray, followed by a CT scan, revealed a pleural effusion, and Salmonella enteritidis was isolated from the pleural fluid. Stool, blood, and urine cultures were negative.Further diagnostics revealed dilated bile ducts, mild thickening of the gallbladder wall, and chronic gastritis. Laboratory findings indicated an elevated erythrocyte sedimentation rate, leukocytosis with neutropenia, and increased levels of C-reactive protein and lactate dehydrogenase. The patient was treated with ceftriaxone. The clinical course was complicated by an ischemic cerebrovascular accident, but the overall outcome was favorable.Conclusion: Pulmonary salmonellosis is rare but can occur in the absence of the typical gastrointestinal symptoms associated with Salmonella infection. Early diagnosis is crucial for successful treatment. In this context, prompt microbiological sampling and the initiation of broad-spectrum antibiotics are essential.
Keywords: Salmonella; pleural empyema; negative stool cultures; negative blood cultures.